Factors Influencing Child Health at the Periphery of the Kumasi Metropolis, Ghana (Journal of Science and Technology, 2016)
The paper examined some of the factors that influence child health at peripheral settlements of the Kumasi Metropolis in Ghana. The simple random technique, supported by purposive procedure, was used to select 240 women whose children were above 2 years but less than 5. Formal interview was the main data collection instrument, whilst linear regression, alongside crosstabulation, was the main analytical tool. Results showed that the principal determinants of child health, in the metropolis were mother's education, household income and exclusive breastfeeding (nutrition). Besides, the use of insecticide bed-nets has been established as having a positive impact on child health. Among the recommendations to improve child health in the locality are the adoption of an integrated approach by appropriate government Ministries and institutions to lift women from the buck of ignorance and poverty through the functional literacy and income generation programmes, whilst steps should be taken to ensure effective formal education of the girl-child. It is recommended that a survey on the impact of childhood immunisation on child health, using a larger sample size, be carried out. A schematic model of the determinants of child health has emerged. This survey has an additional merit of deviating from the normal bivariate and purely descriptive approaches to the use of the multivariate model which evaluates the impact of independent variables.